2011
DOI: 10.1186/2040-7378-3-7
|View full text |Cite
|
Sign up to set email alerts
|

Vascular pathology in multiple sclerosis: mind boosting or myth busting?

Abstract: The investigation of central nervous system vascular changes in the pathophysiology of multiple sclerosis (MS) is a time-honored concept. Yet, recent reports on changes in venous cerebrospinal outflow, the advent of new magnetic resonance imaging techniques and the investigation of immunomodulatory properties of several vascular mediators on the molecular level have added new excitement to hypotheses centering around vascular pathology as determining factor in the pathophysiology of MS. Here we critically revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 78 publications
0
6
1
Order By: Relevance
“…These changes seem to have a different origin from perfusion changes observed in the occipital cortex. They are also different to those observed in MS patients (reviewed in [47] and [48]) and could be associated to the complex and not yet fully understood pathophysiology of NMO [1].…”
Section: Discussioncontrasting
confidence: 60%
“…These changes seem to have a different origin from perfusion changes observed in the occipital cortex. They are also different to those observed in MS patients (reviewed in [47] and [48]) and could be associated to the complex and not yet fully understood pathophysiology of NMO [1].…”
Section: Discussioncontrasting
confidence: 60%
“…Accordingly, this provokes the lysis of erythrocytes and the formation of ''iron sludge,'' which activates inflammation, thus contributing to MS pathology (487). However, a number of established research groups found strong evidence against CCSVI (456). For example, Doepp et al found that only a small population of MS patients has CCSVI according to Zamboni's criteria, and that a large majority of those with CCSVI show no measurable hemodynamic alterations (117).…”
Section: B Circulatory Abnormalities In Pre-ms Brainmentioning
confidence: 99%
“…In a nutshell, CCSVI is not a plausible cause of MS. However, CCSVI should not be confused with anomalies in cerebral blood flow and small veins and venules inside CNS tissue, as accumulating data foster further concepts, which involve vascular changes and obstructed circulation in MS initiation (106,456). Varga et al reported that cerebral blood flow is decreased in the normally appearing white matter (NAWM) of patients with CIS compared with control subjects (449).…”
Section: B Circulatory Abnormalities In Pre-ms Brainmentioning
confidence: 99%
“…In the process of demyelination, the myelin sheath is stripped off neurons in a pattern that follows the venous system [13]. The loss of myelin insulation and plaque formation not only interferes with the transmission of the nerve impulse, but also means loss of support for the neuron, potentially leading to cell death [14]. Eventually the neurodegeneration spreads, encompassing the entire CNS [15].…”
Section: Myelin In the Central Nervous Systemmentioning
confidence: 99%
“…The oxidative stress due to venous haemorrhage and iron deposits can have real implications on the process in demyelination. Aside from MS, iron deposition has been observed in other demyelinating diseases, such as in Hurst acute haemorrhagic leukoencephalitis [14].…”
Section: Vasculature Anomalies In Multiple Sclerosismentioning
confidence: 99%